Accounting for Deferred-Payment Notes - Rogers, Richard L.; Menon, Krishnagopal (The Accounting Review, 1985)
[This article discusses the accounting implications of a new type of financial security introduced on the European bond market. The security, known as a deferred-payment note, allows the investor to acquire a note by paying a portion of the issue price at the time of issuance. The remaining amount is required to be paid in a second installment due some months later. Alternative accounting treatments are presented. These treatments are evaluated in light of the FASB's conceptual framework pronouncements. The paper concludes that the FASB's current position fails to provide appropriate guidelines which the profession can use to resolve this new financial reporting issue.]